Synthesis of Green Carbon Dots from Nephelium Lappaceum L. Seeds - Kamali, Siti Raudhatul; Hamdiani, Saprini; Hermanto, Dhony; Saputri, Dinar Suksmayu; Chen, Chang-Nan (Jurnal Pijar Mipa, 2024)
In this study, rambutan (Nephelium Lappaceum L.) seeds were used to fabricate green carbon dots (gCDs) by employing a hydrothermal process. The synthesized CDs were evaluated using Fourier transform infrared (FT-IR) and X-ray photoelectron spectroscopy (XPS) for the structural properties as well as UV-Vis and fluorescence spectrophotometry for the optical properties. UV-Vis examination revealed that the produced gCDs showed emission-dependent photoluminescence excitation, with two absorption peaks at 265 nm and 330 nm. The presence of functional groups and chemical composition such as C=C, C=O, -COOH, and -OH on the surface of gCDs was confirmed by the results of FTIR and XPS spectra. Consequently, gCDs present several opportunities for exploration in a range of applications.